The Implementation of Islamic Good Corporate Governance at Baitul Maal Hidayatullah, East Java: Strengthening Accountability and Sharia-Based Transparency in Zakat Management - Abdan Syakura; Fidiana; Wahidahwati (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyse the implementation of Islamic Good Corporate Governance (IGCG) at Baitul Maal Hidayatullah (BMH) East Java as a response to declining zakat revenue and increasing demands for transparency in Islamic philanthropic institutions, using a descriptive qualitative approach with data collected through in-depth interviews, field observations, and document analysis to assess the application of IGCG principles within institutional practices. The findings show that BMH East Java has made efforts to implement IGCG, particularly in Sharia supervision and more transparent financial reporting, although several challenges remain, including inconsistency across organisational units, suboptimal stakeholder engagement, and limited use of digital technology. In conclusion, IGCG has the potential to enhance the credibility and performance of zakat institutions when implemented comprehensively and contextually, thus requiring strengthened internal audit systems, improved digital infrastructure, and continuous human resource development through training.